Use of ureteral catheter for under vision suctioning in rigid therapeutic bronchoscopy in children: A novel approach - Krushnakumar V Kesan; Sikha K Kesan; Arvind Ade; Paras Kothari (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Background: Rigid bronchoscopy is a common procedure and treatment of choice for foreign body (FB) in respiratory tract. Blind suctioning using rigid suction cannula is associated with technical difficulties and complications. Under vision flexible cannula are expensive and not commonly available. This led us to discover the alternative of using Ureteral catheters flexible suction cannula for under vision suctioning.  Patients and methods: A retrospective study was conducted in the department of Surgery at tertiary hospitals, from January 2015 to March 2020. Medical records and operative videos were analyzed. Forty two Paediatric patients with foreign body in respiratory tractwere subjected to rigid bronchoscopy and Ureteral catheterwas used as flexible suction cannula for under vision suctioning.  Results: Forty two patients (12 infants, 30 between age 1to 8 year; 26 males and 16 females) with FB bronchus subjected to rigid bronchoscopy. N = 32 were having organic FB and n = 10 were having inorganic (Graph 1), duration of FB in Respiratory tract ranged from 6 hours to 8 months, 7 in main bronchus, 33 having unilateral and 2 having Bilateral FB. Operative time ranged from 15 minutes to 75 minutes. 4 patients had slight intraoperative bleed due to mucosal injury, postoperative stay ranged from 1 to 4 days. Conclusion: Use of Ureteral catheterfor under vision suctioning in rigid bronchoscopy in children quite feasible and effective technique. The main advantages in are simplicity, short operative time, Less traumatic, Good vision, with minimal complications.  Type of study: Treatment Study. Level of evidence: LEVEL IV, Case series with no comparison group.